Dialectics of Low Energy Design, Accessibility, and Materiality in Tropical Urban Crisis - Young, Hepi Duchovny; Setyowati , Erni; Prianto, Eddy; Dwiyanto, Agung (Universitas Ibn Khaldun Bogor, 2025)
This research examines the development of tropical buildings that address the challenges of climate change and population growth by integrating accessibility for all and designing buildings that consume less energy. This research aims to assess the social and technical conflicts between accessibility and energy efficiency, and to develop an evaluation framework based on optimization algorithms that finds a balance between the two. Testing phase change materials (PCMs), energy modelling using Energy Plus, and critical policy analysis employing Critical Discourse Analysis (CDA) are all integral components of the mixed-methods approach. The primary result is that PCMs can help maintain more stable temperatures without requiring significant insulation; however, issues with regulations and design persist. Standard designs may exceed energy limits, but generally make it more challenging to achieve places. Research indicates that to create inclusive and sustainable tropical architecture, it is essential to establish integrated criteria and employ a transdisciplinary approach.